The probiotic and immunomodulation effects of Limosilactobacillus reuteri RGW1 isolated from calf feces - Huang, Kailang; Shi, Weibing; Yang, Bin; Wang, Jiakun (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Limosilactobacillus reuteri is a gut symbiont with multiple remarkable beneficial effects on host health, and members of L. reuteri are valuable probiotic agents. However, L. reuteri showed obvious host specificity. Methods In our study, a novel L. reuteri RGW1 was isolated from feces of healthy calves, and its potential as a probiotic candidate were assessed, by combining in vitro, in vivo experiments and genomic analysis. Results and discussion RGW1 was sensitive to all the antibiotics tested, and it did not contain any virulence factor-coding genes. This isolate showed good tolerance to acid (pH 3.0), 0.3% bile salt, and simulated gastric fluid. Moreover, this isolate showed a high hydrophobicity index (73.7 ± 4.6%) and was able to adhere to Caco-2 cells, and antagonize Escherichia coli F5. Treatment of LPS-induced mice with RGW1 elevated TGF-β and IL-10 levels, while RGW1 cell-free supernatant (RCS) decreased TNF-α levels in the sera. Both RGW1 and RCS increased the villus height and villus height/crypt depth ratio of colon. Genomic analysis revealed the mechanism of the probiotic properties described above, and identified the capacity of RGW1 to biosynthesize L-lysine, folate, cobalamin and reuterin de novo. Our study demonstrated the novel bovine origin L. reuteri RGW1 had multiple probiotic characteristics and immunomodulation effects, and provided a deeper understanding of the relationship between these probiotic properties and genetic features.